THE EFFECT ON DEVELOPMENT OF ENTREPRENEURSHIP EDUCATION MARKETING IN MICRO SMALL MEDIUM ENTREPRISES (SMEs) AT BANDUNG DISTRICT - Muhammad Ridha Rachman; Maria Sugiat (Universitas Muhammadiyah Kalimantan Timur, 2021)
In Bandung district many Micro, Small and Medium Enterprises (SMEs) are not familiar with entrepreneurship education due to limited access to it. Meanwhile, the potential of Micro, Small and Medium Enterprises (SMEs) is enormous, especially in the culinary field. In fact, Micro, Small, and Medium Enterprises (SMEs) can contribute as much as 57.8% of Indonesia's Gross Domestic Product (GDP) revenue. Of course, this phenomenon will affect the business activities of business actors, one of which is the difficulty in developing marketing in their business. This study aims to determine how the influence of entrepreneurship education on marketing development in the culinary for Micro, Small and Medium Enterprises (SMEs) of Bandung District. Data were taken using quantitative methods through a preliminary survey of 50 respondents of culinary Micro, Small and Medium Enterprises (SMEs) in Bandung District. The results show that there is a positive and significant influence of entrepreneurship education on the development of the culinary Micro, Small and Medium Enterprises (SMEs) market in Bandung District. The facts prove that all respondents studied relied on self-taught methods to learn business, without any special education about entrepreneurship given. Therefore, this phenomenon results in the difficulty of marketing development carried out by culinary Micro, Small and Medium Enterprises (SMEs) in Bandung District due to the absence of entrepreneurial education obtained by culinary Micro, Small and Medium Enterprises (SMEs) in Bandung District.